Structure and dynamics of single-chain nano-particles in solution. (22nd November 2016) - Arbe, A.; Pomposo, J.A.; Moreno, A.J.; LoVerso, F.; González-Burgos, M.; Asenjo-Sanz, I.; Iturrospe, A.; Radulescu, A.; Ivanova, O.; Colmenero, J.
Abstract: By means of intramolecular folding/collapse of individual polymer chains (precursors), ultra-small soft nano-objects called single-chain nano-particles (SCNPs) can be synthesized. Here we present a combination of scattering techniques [small angle X-Ray and neutron scattering (SAXS and SANS), neutron spin echo (NSE) and dynamic light scattering (DLS)] to investigate the structure and dynamics of SCNPs in solution and their linear precursors as reference. Coarse-grained molecular dynamics (MD) simulations have also been carried out to complement this study. The application of SANS and SAXS has proved the compaction of the macromolecules upon creation of internal cross-links. However, the SCNPs obtained by different routes exhibit a far from globular topology in good solvent. Regarding the dynamics, we report on the first experimental investigation of the dynamic structure factor of SCNPs in solution. It reveals a clear impact of internal cross-links through (i) a reduction of the translational diffusion coefficient and (ii) an important slowing down of the internal modes. The data have been analyzed in terms of theoretical approximations based on the Zimm model. Both, structurally and dynamically, SCNPs show striking resemblances with intrinsically disordered proteins: similar scaling properties reflecting sparse morphologies and an extremely high internal friction. Graphical abstract: Highlights: Scattering techniques are unique to unveil the structure and dynamics of SCNPs. SCNPs exhibit a far from globular topology in good solvent. Internal cross-link has a great impact in the internal dynamics of macromolecules. SCNPs show striking similarities with intrinsically disordered proteins. MD-simulations offer a great help for the interpretation of experimental results.